Integrating Stability Assessments Under the Financial Sector Assessment Program into Article IV Surveillance-Background Material. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2010)
This paper presents the staff analysis underpinning two central elements of the proposal to make financial stability assessments under the FSAP mandatory for members with systemically important financial sectors: the definition of systemic importance used in the paper and the methodology for identifying members with systemically important financial sectors (Section II); and the review of the literature and industry practices that form the basis for the staff proposal to conduct these mandatory financial stability assessments at a frequency of about three years (Section III).
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet